Presidential dissolution for the legislature - Boukerzaza, Ahmed (Journal of Human Sciences, 2021)
If the law makes one of the contracting parties a right to annul the contrat , the other contracting party cannot uphold that right.In the contracts binding on both sides, if one of the contracting parties fails to fullfill his obligations, the other contracting party may, after notifying the debator, demand the implementation of the contract or its compensation in both cases if the case so requires.